(untitled) (Colombia Medica, 2012)
Introduction: Listeria monocytogenes is a pathogen acquired through the consumption of contaminated foods. Thirteen serotypes have been reported, of which 1/2a, 1/2b, and 4b are responsible for 98% of human listeriosis cases. This study examines the association between serotypes and virulent clones, offering greater information and providing tools to prevent and control diseases caused by L. monocytogenes serotype 4b. Objective: To identify the serotypes from L. monocytogene strains isolated from different samples by performing the molecular subtyping technique; to determine the 85M fragment that codifies for epidemic clone I. Methods : 108 strains of L. monocytogenes were used, isolated from samples of animals, body fluids, foods, and food processing plant equipment and spaces. The samples were identified by following the Bacteriological Analytical Manual protocol described by the Food and Drug Administration (FDA). The strains were identified by Polymerase Chain Reaction (PCR) using primers and a standardized protocol from a previous research project. Serotype identification was performed by multiplex PCR. The determination of the 85M fragment of the SSCS cassette was done by following the protocol by Yildrim et al. Results : Of the 108 L. monocytogenes strains analyzed, 60.2% (65 strains) belonged to the 4b-4d-4e serotype, 17.6% (19 strains) were identified as 1/2a-3a serotype, 14.8% (16 strains) were 4a-4c serotype, 3.7% (4 strains) belonged to the 1/2c-3c serotype, and (3.7%) corresponded to the 1/2b-3b-7 serotype. It was determined that the L. monocytogenes strains serotype 4b-4d-4e and 1/2a-3b have the 85M fragment of the SSCS cassette. Conclusion : This study reports the predominant existence of L. monocytogenes strains serotype 4b-4d-4e in food, environmental, and clinical samples. The presence of an epidemic clone I region was also found in L. monocytogenes strains.